The Harbor Facilities of King Khufu on the Red Sea Shore: The Wadi al-Jarf/Tell Ras Budran System - Tallet, Pierre.
Since 2011, a joint team of the Paris-Sorbonne University and the French Institute in Cairo (IFAO) has been excavating an exceptionally well-preserved harbor complex from the Early Old Kingdom at Wadi al-Jarf along the Egyptian coast of the Red Sea. Considered now to be the oldest port site in Egypt and the first prototype of this kind, it was used for a short time as a departure point to the Sinai Peninsula for royal expeditions on the way to the regions of Serabit al-Khadim and Wadi Maghara, the principal mining areas for copper and turquoise. According to the finds and epigraphy, all these installations date back exclusively to the very beginning of Dynasty 4. In 2013 the site received much scientific attention after the discovery of hundreds of fragments of narrative and administrative papyri, some of them name King Khufu and report various operations linked to the construction site of the Great Pyramid at Giza.Since 2013, the installations along the coastline have been under investigation and revealed all the constitutive elements of a harbor, such as an extensive mole underwater, numerous nautical elements, dwelling and storage buildings with evidence of administrative control and even a large workmen’s barracks. The site at Wadi al-Jarf seems to naturally extend on the west coast of the Sinai Peninsula and a clear connection now has to be considered with the so-called late Old Kingdom fortress at Tell Ras Budran identified on the shore of the El-Markha plain. Based on the Wadi al-Jarf discoveries, its short-term occupation and the pottery evidence, which create a direct link between the sites, the function and chronology of the fortress needs to be completely reassessed and be regarded as a component and the bridgehead of the same ambitious system established at the very beginning of the Dynasty 4 along the two sides of the Gulf of Suez in order to reach the mining areas securely.